STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN DI PUSAT PENGEMBANGAN ANAK IO-0497 BENYAMIN OEBUFU - Yusuf Tanaem; Imelda Djira (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2020)
This study aims to identify strengths, weaknesses, opportunities, and threats and then determine the learning strategy of Christian Religious Education in PPA IO-0497 Benyamin Oebufu. This study used a qualitative method with a descriptive approach and data analysis using a SWOT analysis. The steps in this research are observation and literature study, problem identification and formulation, data collection, data processing, discussion, and conclusion drawing. The subjects in this study consisted of 2 management bodies and four mentors. The results showed that PPA IO-0497 Benyamin Oebufu had 11 strengths, eight weaknesses, six opportunities, and six threats. The results show that the position of the CRE learning strategy in PPA IO - 0497 Benyamin Oebufu is in the Quadrant I area, meaning that growth strategies are possible because strengths are more significant than weaknesses, and opportunities are more significant than threats. The CRE learning strategy at PPA IO-0497 Benyamin Oebufu is the integration of learning with God's Word, applying creative and engaging technology-based Bible learning, building a spiritual community to grow together, conducting competency-building training for mentors, and conducting pastoral counselling for children and parents.